Birds Biting Back: A Study of Deliberateness and Species Protection Under the Birds Directive After Voore Mets - Toikka, Aino (My University, 2026)
This thesis examines the impact of the Voore Mets judgment on the interpretation of ‘deliberate’ harm under the EU Birds and Habitats Directives and evaluates what this development reveals about the Birds Directive as a part of EU biodiversity regulation framework. In Voore Mets the Court of Justice of the European Union defined what ‘deliberate’ harm means under the Birds Directive when tree felling during bird breeding season was considered. The thesis outlines the relevant background of the Nature Directives and their species protection regimes and locates them within their broader global and European context. The definition of ‘deliberateness’ and its role in the Birds Directive is analysed through a doctrinal legal method grounded in the text of the Directives and the case-law of the Court. The study also applies a law-in-context approach by examining the regulatory background of the Birds Directive and the wider structure of EU environmental law in order to situate the discussed concepts and the judgment within their legislative framework. The thesis traces the evolution of ‘deliberate’ under the case-law of Article 12 of the Habitats Directive and Article 5 of the Birds Directive, the provisions on species protection of animal and bird species. It is demonstrated that Voore Mets confirms a harmonised, knowledge-based minimum threshold of deliberateness, according to which deliberateness is fulfilled when an actor was aware of and accepted the possibility of harming protected species, regardless of whether the act was purposefully intended to cause harm. The judgment also affirms that the prohibitions in the Birds Directive regarding deliberate killing, capture or destruction of eggs or nests apply no matter the population level of the species, extending equally to common and rare species. This is argued to be a convincing interpretation in light of the text and structure of the Birds Directive and previous case-law. The thesis also presents critical observations regarding the judgment. It is argued that Voore Mets demonstrates the relative strictness of the Birds Directive, and that it reveals the weakness of the Directive’s derogation system, as economic interests are not expressly recognised in the derogation grounds of Article 9. The judgment may lead to a situation in which the balancing of economic rights cannot be carried out directly when applying the Directive, thus requiring the invocation of the EU Charter of Fundamental Rights. The thesis also notes that the judgment may lead to significant administrative obligations for forestry operators. The thesis concludes that Voore Mets strengthens the preventive nature of environmental protection under the Birds Directive’s species protection regime. This marks it as relatively strong from an environmental perspective when contrasted with the discourse surrounding other environmental instruments.

Tässä tutkielmassa tarkastellaan Voore Mets -tuomion vaikutusta EU:n lintu- ja luontodirektiivien mukaisen ”tahallisen” vahingoittamisen tulkintaan, sekä arvioidaan, mitä tämä kehitys paljastaa lintudirektiivistä osana EU:n biodiversiteettisääntelyä. Voore Mets -tuomiossa Euroopan Unionin tuomioistuin määritteli, mitä ”tahallinen” vahinko tarkoittaa lintudirektiivin nojalla silloin, kun metsähakkuita harjoitetaan lintujen pesimäaikana. Tutkielma esittelee direktiivien taustaa ja niiden lajiensuojelujärjestelmiä sekä sijoittaa ne laajempaan globaaliin ja eurooppalaiseen kontekstiin. Tahallisuuden merkitystä ja sen roolia lintudirektiivissä analysoidaan oikeusdogmaattisesti, perustuen direktiivien tekstiin ja unionin tuomioistuimen oikeuskäytäntöön. Tutkimuksessa oikeutta tarkastellaan kontekstuaalisesti analysoimalla lintudirektiivin sääntelytaustaa ja EU:n ympäristöoikeuden rakenteita, mikä mahdollistaa käsitteiden sekä kyseisen tuomion merkityksen sijoittamisen niiden oikeudelliseen viitekehykseen. Tutkielmassa jäsennetään tahallisuuden käsitteen kehitystä eläin- ja lintulajien suojelua koskevien säännösten eli luontodirektiivin 12 artiklan ja lintudirektiivin 5 artiklan oikeuskäytännössä. Analyysi osoittaa, että Voore Mets vahvistaa harmonisoidun, tekijän tietoisuuteen ja riskin hyväksymiseen perustuvan tahallisuuden vähimmäistason, jonka mukaan tahallisuus täyttyy, kun toimija on ollut tietoinen vahingon mahdollisuudesta ja on hyväksynyt sen, riippumatta teon varsinaisesta tarkoituksesta. Tuomio vahvistaa myös, että lintudirektiivin kiellot, jotka koskevat tahallista tappamista, pyydystämistä sekä munien tai pesien tuhoamista soveltuvat riippumatta kyseisen lajin populaatiotasosta, eli ne ulottuvat yhtä lailla sekä yleisiin että harvinaisiin lajeihin. Tätä pidetään vakuuttavana tulkintana lintudirektiivin sanamuodon ja rakenteen sekä aiemman oikeuskäytännön valossa. Tutkielmassa esitetään myös kriittisiä huomioita tuomiosta. Tutkielmassa argumentoidaan, että Voore Mets osoittaa lintudirektiivin olevan suhteellisen tiukka, ja että sen poikkeusjärjestelmässä on heikkouksia, sillä taloudellisia etuja ei ole nimenomaisesti tunnustettu 9 artiklan poikkeusperusteissa. Tuomio voi johtaa tilanteeseen, jossa taloudellisten oikeuksien punninta ei ole mahdollista suoraan direktiiviä sovellettaessa, vaan edellyttää vetoamista EU:n perusoikeuskirjaan. Tutkielmassa todetaan myös, että tuomio voi johtaa merkittäviin hallinnollisiin velvoitteisiin metsätalouden toimijoille. Tutkielma päätyy siihen, että Voore Mets vahvistaa lintudirektiivin lajisuojelujärjestelmän ennaltaehkäisevää luonnetta. Tämän seurauksena direktiivi näyttäytyy ympäristönäkökulmasta suhteellisen vahvana verrattuna keskusteluun muista ympäristöoikeudellisista sääntelyvälineistä.
Keywords: EU environmental law; Birds Directive; Habitats Directive; deliberate; Voore Mets; species protection; derogation; EU-ympäristöoikeus; lintudirektiivi; luontodirektiivi; tahallisuus; lajiensuojelu; poikkeaminen